Schistosomiasis - Fenwick, Alan (Henry Stewart Talks, 2011)
Introduction to Schistosomiasis, Prevalence of the parasitic worm in Africa, Lifecycle of the worm, Consequences of infection in children, Consequences of infection in later life, Effectiveness of protecting children, Current initiatives